2016
DOI: 10.1111/jocn.13424
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses’ knowledge and practice of venous thromboembolism risk assessment and prevention in South Korea: a cross‐sectional survey

Abstract: Focused education on venous thromboembolism prevention and risk assessment should be considered a component of continuing education for Korean nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
3
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 20 publications
6
40
3
10
Order By: Relevance
“…This result agrees with (Oh et al,2017) who stated that most of participants rated their VTE knowledge were fair or poor. This may be related to the low level of inservice continuous education regarding venous thromboembolism risk assessment and prevention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result agrees with (Oh et al,2017) who stated that most of participants rated their VTE knowledge were fair or poor. This may be related to the low level of inservice continuous education regarding venous thromboembolism risk assessment and prevention.…”
Section: Discussionsupporting
confidence: 91%
“…The risk of developing a thrombus is often described with Virchow's triad, which includes venous stasis, endothelial injury, and hypercoagulability of the blood. (Oh, Boo &Lee, 2017 ;Stone, Hangge & Albadawi, 2017) Pulmonary embolism as a subsequent event after DVT is critical and is one of the leading causes of death for many patients. Most PEs originates from DVTs of lower extremities, and approximately 50% of DVT may lead to silent PE.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 14 ] A previous study demonstrated that only 9% of participants in South Korea received in-service continuous education. [ 15 ] This is relatively, low compared with our results, which may be related to the fact that our respondents were recruited from the best hospitals (AAA-grade) in China. Nurses at these hospitals pay greater attention to VTE prophylaxis and receive frequent training.…”
Section: Discussioncontrasting
confidence: 67%
“…1 showed, 40.3% of participants knew the indications for GCS, and 36.0% of participants knew the contraindications for GCS. The study of Oh, Boo, and Lee [ 7 ] also stated that the mean score was 3.39 (± 0.95) out of a possible score of 5 for effective use of mechanical devices for VTE prevention (e.g., GCS, intermittent pneumatic compression, or a foot pump). All these suggested healthcare professionals’ knowledge of clinically applying GCS was deficient to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The survey found that the overall mean score of the practice of clinically applying GCS was 16.94 (± 5.81) out of a possible score of 30, and only 30.4% of the medical staffs’ behavior when applying GCS was standardized, which might be due to the low level of knowledge and lack of training. Many studies [ 7 , 9 – 11 ] have shown that nurses lack VTE training and their behavior is not regulated. The majority of the sample were nurses (81.9%), which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%